Modeling of the material removal rate in internal cylindrical plunge electrochemical grinding. (28th April 2023) - Ma, Xiaosan; Jiao, Feng; Niu, Ying; Wang, Xue; Hu, Zhanzhan; Bie, Wenbo; Yang, Guangbin
Abstract: The material removal rate (MRR) in the internal cylindrical plunge electrochemical grinding (ICPECG) is hard to assess because it involves two feed motions: workpiece circumferential rotation and grinding wheel motion in the radial direction. This study attempts to model the MRR and electrochemical overcut in the stable grinding stage of ICPECG by using an equivalent plane electrochemical grinding model with a single feed motion. The differential equation of the interelectrode gap (IEG) in the machining area in the stable grinding stage of ICPECG is derived. Then, based on Faraday's electrolytic law, MRR models of electrochemical anode dissolution (EAD), abrasive mechanical grinding, and electrochemical overcut depth are established and numerically simulated by a variable replacement under different machining parameters. The numerical results indicate that the grinding wheel's radial feed rate most significantly influences the EAD share in the total MRR. In contrast, the power supply voltage mainly controls the electrochemical overcut depth. The proposed model's feasibility and revealed correlations are experimentally verified.